Changes in the Clinical and Pathological Characteristics of Gastric Cancer during the Last 16 Years: A Study of a Single Institution in Korea - Jung Won Lee; Nayoung Kim; Yong Jae Kwon; Hye Seung Lee (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Background/Aims The incidence of gastric cancer (GC) in Korea is very high compared to that in other countries. The aim of this study was to investigate the trends of GC in patients for over 16 years. Materials and Methods A total of 1,227 patients with GC were prospectively enrolled at Seoul National University Bundang Hospital between 2003 and 2018. Age, sex, histologic type (Lauren classification), and Helicobacter pylori (H. pylori) infection status were compared between three periods (2003~2007, 2008~2012, and 2013~2018). H. pylori infection status was evaluated based on histology, rapid urease test, culture, serology, and history of H. pylori eradication. Patients with severe atrophy or intestinal metaplasia based on histology were assumed to have previous H. pylori infection. Results Most patients with GC underwent endoscopic mucosal resection/endoscopic submucosal dissection or another type of surgery. Early GC (EGC) and advanced GC (AGC) were detected in 769 (62.7%) and 458 (37.3%) patients, respectively, and intestinal and diffuse types were detected in 714 (58.2%) and 485 (39.5%) patients, respectively. The prevalence of EGC increased from 54.0% (252/467) to 63.5% (359/565) to 81.0% (158/195) in 2003~2007, 2008~2012, and 2013~2018, respectively. The prevalence of H. pylori-positive GC decreased from 93.4% (436/467) to 88.5% (500/565) to 82.1% (160/195) during these three periods, respectively (P<0.001). Multivariate logistic analysis showed that diffuse-type GC was continuously more prevalent in those who were younger than 50 years, who were female, and who harbored the predominant AGC type. Conclusions Over 16 years, the prevalence of EGC increased with a decrease in H. pylori infection rate. Diffuse-type GC was continuously more common in young and female patients.